2016
DOI: 10.1039/c6cp05848e
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of nine berberine salts in the solid state: optimization of the photoluminescence and self-association properties through the choice of the anion

Abstract: The arrangement of an ionic fluorophore in the crystalline state was regulated by the presence of various counter-ions and the effect on spectroscopic and self-association properties was studied. To do so, nine salts of berberine (i.e. a fluorescent natural alkaloid) were investigated. Most of them contained organic anions and were prepared using an ion-exchange process. Berberine chloride and hemisulfate were also used for the sake of comparison. The diffuse reflectance and photoluminescence spectra were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…1A) by ionassociation. [79][80][81][82][83][84][85] For this, we mixed TPE-DPA-Py iodide (2 μM) with a 10-fold molar excess of the corresponding counterions in water. Dynamic light scattering (DLS) measurements showed that TPE-DPA-Py iodide in the presence of counterions forms relatively small particles ranging from ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A) by ionassociation. [79][80][81][82][83][84][85] For this, we mixed TPE-DPA-Py iodide (2 μM) with a 10-fold molar excess of the corresponding counterions in water. Dynamic light scattering (DLS) measurements showed that TPE-DPA-Py iodide in the presence of counterions forms relatively small particles ranging from ca.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, both TPE-F5 and TPE-F12 exhibited typical AIE behaviour, in line with other AIEgens reported earlier. 43,78,82 Remarkably, the emission maximum of TPE-F5 and TPE-F12 in water reached NIR region ~700 nm. On the other hand, the AIE experiments using dye salts with smaller counterions (TPE-PF6 and TPE-ClO4) also showed AIE behaviour, and their fluorescence quantum yields at 80% water were even higher than those with bulky anions.…”
Section: Aie Behaviour Of Tpe-dpa-py With Different Counterionsmentioning
confidence: 94%
“…Toward fluorescent materials, new approaches have employed the co-assembly of cationic dyes with large anions. [37][38][39] Most successful are the works of Reisch and Klymchenko that obtained very high brightnesses using a covalently modified cationic rhodamine dye that was also ion paired with bulky fluorinated anions to become lipophilic and then loaded into polymer nanoparticles. [40][41][42] Despite the ability to translate optical properties, under the appropriate conditions, most of the assemblies do not display the crystalline ordering expected from use of strong structure-directing units.…”
Section: Articlementioning
confidence: 99%
“…In this study, we provide more direct evidence of proton transfer between the drug cation and LS – anion through an analysis of crystal structure, from which molecular insights into the changes in pharmaceutical properties, such as solubility and dissolution rate, could be gained. Crystal structures of a handful of complexes between LS – and organic molecules have been reported, including berberine, 9-aminoacridine (a cationic dye), O- lauroylethanolamine, and quinolinium and isoquinolinium (ionic liquid crystals) . However, most reported drug–lauryl sulfate complexes are amorphous, except for trimethoprim and metformin, which precipitated out as crystalline solids. , Single-crystal structures of trimethoprim and metformin complexes with LS – have not been reported.…”
Section: Introductionmentioning
confidence: 99%